Objective assessment of tinnitus laterality - Mehrnaz Shoushtarian; Jamal Esmaelpoor; Michelle M.G. Bravo; James B. Fallon (PLoS ONE, 2025)
Tinnitus is a condition which involves hearing sounds not present externally. This common condition can lead to a range of symptoms, including depression, resulting in a severe impact on quality of life. There are currently no reliable treatments for tinnitus. One factor hindering development of treatments is the lack of identified subtypes of tinnitus with different underlying patterns of neural activity to enable more personalised treatments and more accurate monitoring of treatment effects. It has been suggested that the perceived laterality of tinnitus, i.e., whether the sound is perceived unilaterally or bilaterally, characterizes tinnitus subtypes with different underlying neural changes. Our previous work showed sensitivity of a non-invasive brain imaging technique called functional near-infrared spectroscopy (fNIRS), to tinnitus-related changes in brain activity. In this study we aimed to investigate differentiating unilateral and bilateral tinnitus using fNIRS recordings and functional network analysis. We performed fNIRS recordings on 18 individuals with unilateral tinnitus (11 left-sided and 7 right-sided), 26 individuals bilateral tinnitus and 18 controls. fNIRS signals were recorded at rest and in response to auditory and visual stimuli. Using network analysis applied to fNIRS recordings, we derived modules characterized by strong connectivity among channels within a module and weak connectivity among channels in different modules. We then calculated two measures, Module Laterality and Modified Module Laterality, to quantify asymmetry in modules. Our findings showed significant difference in Module Laterality in individuals with unilateral tinnitus compared to both bilateral tinnitus and controls. Within the unilateral tinnitus group, Modified Module Laterality showed significant difference between individuals who experienced left-sided tinnitus compared to right-sided tinnitus. Differentiating tinnitus with distinct laterality precepts has the potential to assist in developing and monitoring relevant treatments by revealing neural mechanisms related to each subtype.